LEVEL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH MENENGAH PERTAMA YANG DIBELAJARKAN DENGAN MODEL KOOPERATIF TIPE TTW - Nuralam Nuralam; Zahara Mustika (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2021)
The study on the mathematical communication skills of the junior high school students studied were still not optimally reached that students' mathematical communication skills become optimal by being taught through the TTW type. The purpose of this study is to describe the level of mathematical communication skills taught through of TTW type cooperative learning model rather than expository learning model and describe students' response to TTW type of cooperative learning model. This research uses quasi experiments. The population is students of Abdya Junior High School grade VIII and the sample was cluster random sampling. Data collected and it also the instrument by test and questionnaire. Data analysis techniques used descriptive analysis and inferential. The results of the research showed that (1) the level of mathematical communication skills taught through of TTW type cooperative learning model rather than expository learning model and (2) the response of students after being taught through the TTW type of cooperative learning model was very positive.